Informational Efficiency of World Oil Markets: One Great Pool, but with Varying Depth - Marc Gronwald; Sania Wadud; Kingsley Dogah (Center for Economic Studies and ifo Institute (CESifo), 2024)
This paper investigates the informational efficiency of global crude oil markets using a recently introduced quantitative measure for market inefficiency. The methodology assesses the deviation of observed oil price behavior from the Random Walk benchmark, representing an efficient market. The main findings of the analysis are as follows: firstly, the degree of crude oil market inefficiency demonstrates temporal variations. Secondly, there are marked increases in the degree of inefficiency during extreme episodes, such as the price downturns experienced in 2008, 2014, and early 2020. Thirdly, the degree of inefficiency exhibits substantial variations across regional crude oil markets before 2006 but converges thereafter. Since this discovery is grounded in the observation of more similar price behavior across markets post-2006, the paper establishes a connection between the literature on oil market integration and that focusing on the informational efficiency of oil prices.
Keywords: C22; E30; G14; Q02; Q31; 330; world oil markets; efficient market hypothesis; market integration; fractional integration